CIVIL RIGHTS IN THE DIGITAL WORLD: PROTECTION OF PERSONAL DATA - Abdreymov Yusupbay Turdıbaevich; Alauaddinova Albina Aybekovna (Bright Mind Publishing, 2025)
The article is dedicated to pressing issues of personal data security in the modern digital world.
Keywords: Personal data, cybersecurity, digital world, legislation of Uzbekistan, identification, online security.